Rights of self-determination in case of Nagorno Karabakh. Status quo and possibilities after the 2020 ceasefire - Ādamsons, Jānis (Riga Graduate School of Law, 2022)
The region of Nagorno Karabakh has been in constant on and off-going conflict since the end of the Cold war and the majority of Caucasus region, which includes Armenia and Azerbaijan. Nagorno Karabakh has been in the interest of both since it has become a question of who has the right over the mountainous region. The most pressing matter in the relation to this is the fact that both of the states had used military means and made serious humanitarian breaches, despite the outcry from the international community both sides have made at best temporary ceasefires, which have been breached on and off. The main issue in the dispute is the claim made by the region itself, as it has declared its independence, despite that no one has recognized in the international community and the event has complicated the whole situation.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Right of self-determination; Nagorno Karabakh; Armenia; Azerbaijan